Efficacy of long-term noninvasive positive pressure ventilation in stable hypercapnic COPD patients with respiratory failure: a meta-analysis of randomized controlled trials - Liao, Hao (Int J Chron Obstruct Pulmon Dis, 2017)
INTRODUCTION: The efficacy of long-term noninvasive positive pressure ventilation (NPPV) in stable hypercapnic COPD patients with respiratory failure remains unclear. The aim of this meta-analysis was to critically assess the efficacy of long-term NPPV on mortality, acute exacerbation, exercise capacity, symptoms and significant physiological parameters (lung function, respiratory muscle function and gas exchange). PATIENTS AND METHODS: We performed an electronic literature search using the PubMed, Cochrane Library, Embase, OVID and Chinese Biomedical Literature Database in May 2017. Studies comparing treatment effects of NPPV with oxygen therapy in stable hypercapnic COPD patients with respiratory failure were conducted, and at least one of the following parameters were reviewed: frequency of acute exacerbation, mortality, lung function, respiratory muscle function, gas exchange, exercise capacity. RESULTS: Seven studies with 810 subjects were identified. The partial pressure of arterial carbon dioxide (PaCO(2)) significantly decreased in patients who received long-term NPPV (weighted mean difference [WMD] −3.73, 95% CI: −5.83 to −1.64, P=0.0005). No significant difference was found in mortality, partial pressure of arterial oxygen (PaO(2)), frequency of acute exacerbation, lung function, respiratory muscle function and exercise capacity. The subgroup analysis showed that NPPV significantly improved the survival of patients when it was targeted at greatly reducing hypercapnia (WMD 0.35, 95% CI: 0.19 to 0.64, P=0.0006). CONCLUSION: The results indicate that long-term NPPV decreases the PaCO(2) of stable hypercapnic COPD patients with respiratory failure and improves mortality with the aim of reducing PaCO(2).